SUSTAINABILITY AND UNSUSTAINABILITY ASPECTS OF INTEGRATION OF NOVICE TEACHERS IN THE SECONDARY SCHOOL SETTING - Zhukova, Olena; Pipere, Anita; Iliško, Dzintra; Badjanova, Jeļena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Teachers are being identified as key actors for ensuring quality education, therefore they need to receive a proper professional support during their first years of work in overcoming initial challenges. As the preliminary research indicates, support that they gain is systemic and fragmentary. The aim of the study is to explore the sustainability and unsustainability aspects of integration of novice teachers in the secondary school system. The research methods employ are semi-structured interviews with fourteen teachers on their adaptation experience in the school system, considering both obstacles and factors of success. Research indicates that novice teachers leave their work within the first three years of teaching by finding demands too high and workload sometimes unmanageable. The authors offer suggestions for a more efficient and coherent process of mentoring and professional development of novice teachers.